Global, regional, and national burden of uterine fibroids in the last 30 years: Estimates from the 1990 to 2019 Global Burden of Disease Study - Cheng, Lin-Can; Li, Hao-Yang; Gong, Qin-Qin; Huang, Cheng-Yang; Zhang, Chao; Yan, Jin-Zhu (Frontiers in Medicine, 2022)
Objective: To study specific information on trends in incidence, mortality, DALYs and the corresponding trends among five sociodemographic index regions, 21 regions, also 204 countries for decision making, which would enable policymakers to distribute limited resources and device policies more rationally. Methods: UFs data from 1990 to 2019, including incidence, mortality, and DALYs, were obtained from the 2019 Global Burden of Disease Study. Estimated annual percentage change (EAPC) was calculated to assess morbidity, mortality, and DALYs trends. Results: The incident cases of UFs had obviously increased from 5,769,658 (95%UI, 7,634,3995-4,274,824) incidences in 1990 to 9,643,336 (95%UI, 7,178,053-12,714,741) incidents in 2017, and the age-standardized incidence rate was steady with 225.67/100,000 persons (95%UI, 167.33-298.87) in 1990 to 241.18/100,000 persons (95%UI, 179,45-318.02) in 2019. The ratio of incidence in high socio-demographic index (SDI) region showed a unimodal distribution, with peaks in 2005. Between 2009 and 2017, the age-standardized death rate of UFs declined globally, especially in low SDI and low-middle SDI regions. In contrast with 860,619 DALYs (95%UI, 473,067-1,505,289) in 1990, the number of DALYs was 1,378,497 (95%UI, 710,915-2,475,244) in 2019 which had soared a lot, whereas, the age-standardized DALYs rate decreased expressively with an EAPC of -1.93 (95%CI, from -2.16 to -1.71). Conclusion: The global burden of UFs had been increasing between 1990 and 2019, which the incidences and DALYs increased prominently worldwide, while the deaths of UFs had no evident growth. Lower SDI regions had carried an incremental burden of UFs while disease reduction was observed in higher SDI regions. It is high time to need pay more attention to underprivileged regional quality of life and health protection.